Um modelo para estimativa do consumo de energia de desktops virtuais - Bignatto Junior, Pedro Wilson (Universidade Federal de São Carlos, 2016)
The virtualization of computing resources is becoming increasingly frequent for several purposes. An example is desktop virtualization, in which the user’s workstation is virtualized, executed in a data center, and delivered to users as a service. Users can access their virtual desktops over the network, from anywhere, anytime, using simplified clients as smartphones or tablets. Besides mobility, desktop virtualization brings significant reduction in management costs and administration of desktops. In the present work we propose a model that estimates the energy consumption of a desktop virtualization service. The proposed model aims to assist decision-making on the provision of resources and improving energy efficiency. The model takes into account energy consumption during all the lifecycle of a virtualized desktop since the instantiation. From the experiments, applying the model, it was concluded that for applications with low transmission rate of frames and commands, such as a web browser, it is better to instantiate an VD instead of running as a local desktop. It happens because the energy cost of running is amortized through the sharing of resources between the various connected users into the server, in addition to the low cost of transmission. The best energy efficiency has been obtained as a result of instantiating an VD on a datacenter (DC) with acessible through a local area network (LAN), in which the energy consumption per bit transmission is suffucuently low to compensate energy cost of VD migration between different DCs.
Keywords: Computação em nuvem; Desktops virtuais; Estimativa energética em desktops virtuais; Controladores de nuvem; Eficiência energética em desktops virtuais; Cloud computing; Desktops virtuais; Energy estimate on virtual desktops; Cloud controllers; Energy efficiency in virtual desktops; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO